MENINGKATKAN KEMAMPUAN LOMPAT TINGGI GAYA STRADDLE MENGGUNAKAN BALOK BERJENJANG BAGI SISWA KELAS V SD NEGERI 2 KERTANEGARA KECAMATAN KERTANEGARA KABUPATEN PURBALINGGA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Problems in Elementary School 2 Kertanegara the low ability of the high jump in the fifth grade students ofSD Negeri 2 Kertanegara. This is caused by: 1). Students lacking the spirit of love and learning while followingthe high jump, 2). Students fear the time will jump over the bar, 3). Direct instructional technique oriented andless varied, causing students to be tired or lazy in learning to follow high jump. The purpose of this research isto improve the learning ability of students in the high jump straddle style through the use of tools which areprepared tiered wooden beams in the fifth grade students of SD Negeri 2 Kertanegara.In this study, the method used was Classroom Action Research (CAR). PenelitianTindakan Class (PTK)was held at SDN 2 Kertanegara District Kertanegara Purbalingga in class V. Classroom action researchsubjects are all fifth grade students of SDN 2 Kertanegara by the number of students 34 children, Son: 16children and Daughter: 18 children. PTK declared successful, this is evidenced by the increase in the indicators of success psychomotor aspects of35.75% first cycle and second cycle as much as 98.50%. On the cognitive aspects of the first cycle increased asmuch as 66.18% and 83.24% as much as the second cycle. At the affective aspects of the first cycle increased by38% and the second cycle by 99%. Result of learning styles straddle high jump at the first cycle and second cycleincreased significantly by an increase in the cognitive aspects of 17.06% on the affective aspect of an increase of65% and an increase of psychomotor aspects of 62%. Conclusions from the above results that the use of tieredbeams can improve learning outcomes straddle style high jump at the fifth grade students of SD Negeri 2Kertanegara by 85%. Suggestions for teacher Penjasorkes, that learning style straddle high jump with a tieredbeams can be used as an alternative to the strategy / learning methods and learning can be packaged in a waythat is PAIKEM learning methods of active learning, innovative, creative, effective, and fun.